Risk Factors in Patients with Intrauterine Fetal Death at Tertiary Referral Centre - Sinha, Kavita; Pandey, Subhash (Journal of Nepalgunj Medical College, 2019)
Background: Among various community health indicators available for measurement of quality and impact of health services in developing countries, perinatal mortality accounts one of the top most single indicators even today. Documentation and evaluation of the etiology and the associated risk factors for stillbirth is required in order to decrease the fetal mortality rate and to devise plan in maternal health sector. Objective: To find out common risk factors in patient and its association with intrauterine fetal death. Methods: A hospital based cross-sectional study carried out in the Department of OBSGYN, Nepalgunj Medical College, Kohalpur from Jan 2018 to September 2019.Cases of multiple pregnancies, intrapartum death and fetal death diagnosed before 28th weeks of gestation were excluded. After exclusion, 65 cases of intrauterine fetal death were studied. Results: Majority (78.4%) of the patients with IUFD belonged to the reproductive age group(20-35yrs) and (15.4%) belong to <19yrs (p=0.008) associated with illiteracy (84.6%). More than half (58.5%) had at least one ANC visit and were primigravida (17%) with preterm (63.07%). Hypertensive disorder was the commonest obstetric complication in these mothers (36.92%) followed by unexplained (26.15%), anaemia (18.46%), PROM (15.4%), APH (13.8%). Most of the babies were low birth weight (63.69%) and majority were males (63.1%). Conclusion: Majority of the risk factors found in the present study were preventable. Stillbirth rate can be reduced by proper management of these risk factors during antenatal care and intrapartum care.